Preaching the Red Stuff: J.B. McLachlan, Communism, and the Cape Breton Miners, 1922-1935 - Manley, John (Labour / Le Travail, 1992)
During the early 1920s the Communist Party of Canada (CPC) established a significant presence in industrial Cape Breton, based on support from the militant minority of the district's unusually combative coal mining union, UMWA District 26, and its charismatic Secretary-Treasurer James Bryson McLachlan. The latter's early recruitment was centrally important in forging what would become enduring political links with rank-and-file militants; it was largely thanks to McLachlan that, through all the ebb and flow of social context and human agency, the party survived the vicissitudes of deteriorating structural conditions and its own tactical blunders (most notably during the ‘third period’), to emerge in the mid-130s with genuinely optimistic prospects. The Scot did not always lead his forces well: like many revolutionary contemporaries his bolshevik temperament was ill-suited to defensive struggle. He nevertheless perceived, and to a limited extent acted upon, the need to construct a defensive communist counter-culture within the struggle for workers' power in the community and the workplace. The embodiment of bolshevik intransigence, McLachlan offered a fixed rallying-point for ‘class fighters,’ especially those who shared his internationalist perspective. Having drawn a new layer of younger militants towards him in 1934-35—and having seen off the CCF in the process—McLachlan could claim to have placed the CPC in its strongest position for a decade.
Keywords: Coal mines & mining; Communism; Communist Party of Canada; History; McLachlan, J.B. (James Bryson); United Mine Workers of America